Dual Primary Malignancy: A Rare Organ Combination. (7th October 2014) - Acharya, Preetam; Ramakrishna, Anand; Kanchan, Tanuj; Magazine, Rahul
Abstract : A 63-year-old female smoker was evaluated for lump over the right breast, fine needle aspiration cytology of which showed infiltrating ductal carcinoma. Investigations also revealed the presence of left upper lobe mass lesion, the biopsy of which suggested small cell carcinoma. The existence of two malignancies having different histopathologies at anatomically distinct sites suggests the diagnosis of dual primary malignancy involving the breast and the lung which, being a rare combination, prompted us to report the case.